Perioperative Haemorrhage in Transurethral Resection of Prostate: Impact of 5 Alpha Reductase Inhibitors in the Reduction of Perioperative Blood Loss - Ahamad, Mohamad Anish; Tiwari, Jonesh; Ansari, Emran; Joshi, Manisha (Med Phoenix, 2023)
Introduction: Benign prostatic hyperplasia (BPH) is an age dependent disorder characterized by hyperplasic changes in the tissue resulting in enlargement of the prostate that may lead to difficultly in micturition or impairment in the flow of urine from the bladder. Medical treatment is the primary option for the patient with mild to moderate voiding symptoms which consists of alpha blockers and 5-alpha reductase inhibitors either as mono-therapy or in combination therapy.Materials and Methods: A observational cross-sectional study was conducted in a teaching hospital. Total sixty-four patients were selected from hospital records. Group-A received Alpha blocker along with Dutasteride while group-B received Alpha blockers only as a primary medical treatment two weeks prior to transurethral resection of prostate for benign prostatic hyperplasia. Patients were followed up after 24 hours of surgery in which hematocrit levels were estimated. Blood loss was calculated by recording pre-operative and post-operative (after 24 hours) hematocrit level. Data were tabulated and analyzed by SPSS v25. Comparison of two groups’ Group A Alpha-blocker with Dutasteride and Group B with Alpha-blocker only was done by applying independent sample t-test. A p-value ≤0.05 was taken as significant.Results: A total of 64 patients were enrolled for this study. Patients were divided into two groups i.e. Group-A (TURP with Alpha-blocker &Dutasteride) and Group-B (TURP with Alpha-blocker). Mean age of group-A patients was 66.4±7.5 years and 66.5±7.2 years in group-B. Mean blood loss of group-A patients was 158.3±131.1 ml and 311.5±150.7 ml in group-B with a p-value of 0.000054, which is statistically significant.Conclusion: Patients on Dutasteride have less perioperative bleeding during transurethral resection of prostate for benign prostatic hyperplasia.